The gut microbiome in konzo - Matthew S. Bramble (Nature Portfolio, 2021)
Here, using metagenomic profiling in 180 individuals from the Democratic Republic of the Congo, the authors find associations between the gut microbiome and konzo, a neurodegenerative disease that mostly affects children and is caused by the consumption improperly processed cassava.